The therapeutic potential of non-invasive brain stimulation for the treatment of Long-COVID-related cognitive fatigue - Linnhoff, Stefanie; Koehler, Lilli; Haghikia, Aiden; Zaehle, Tino (Frontiers in Immunology, 2023)
Following an acute COVID-19 infection, a large number of patients experience persisting symptoms for more than four weeks, a condition now classified as Long-COVID syndrome. Interestingly, the likelihood and severity of Long-COVID symptoms do not appear to be related to the severity of the acute COVID-19 infection. Besides dyspnoea, chest pain, olfactory disturbances, and brain fog, fatigue is amongst the most common and debilitating symptoms of Long-COVID. It is also frequently reported in many other neurological diseases, affecting a broad range of everyday activities. However, despite its clinical significance, limited progress has been made in understanding its causes and developing effective treatment options. Non-invasive brain stimulation (NIBS) methods offer the unique opportunity to modulate fatigue-related maladaptive neuronal activity. Recent data show promising results of NIBS applications over fronto-parietal regions to reduce fatigue symptoms. In this current paper, we review recent data on Long-COVID and Long-COVID-related fatigue (LCOF), with a special focus on cognitive fatigue. We further present widely used NIBS methods, such as transcranial direct current stimulation, transcranial alternating current stimulation, and transcutaneous vagus nerve stimulation and propose their use as possible therapeutic strategies to alleviate individual pathomechanisms of LCOF. Since NIBS methods are safe and well-tolerated, they have the potential to enhance the quality of life in a broad group of patients.